Doing Ethnography Remotely: Rethinking Methodologies of Fieldwork in Gabura of Southwest Bangladesh during the Global COVID-19 Pandemic - Zaid, Fahmid Al (Social Science Review, 2023)
This article describes the possible processes of conducting ethnographic fieldwork remotely through mediated ways among the Gabura Islanders in Southwest region of Bangladesh during the global COVID-19 pandemic. As observed, due to the impact of COVID-19, a crisis of choosing the ‘field’ and conducting ‘fieldwork’ has taken place in writing ethnography that requires both methodological and theoretical rethinking. However, the basic of anthropological fieldwork is physical immersion into the culture as much as possible. Also, it has become nearly impossible to conduct field research in such an intimate way during the period of COVID-19. The COVID-19 pandemic situation has forced the ethnographers to stay home and have had to find new way of gaining access to the field. To this backdrop, this article depicts the possible processes of conducting ethnographic fieldwork through mediated ways such as using digital communications and engaging research assistant in the data collection process. Thus, the article presents author’s own experiences and challenges of doing ethnography remotely through mediates ways by gaining rapport and making interaction with the Gabura Islanders in Southwest Bangladesh during the covid-19 pandemic. Nevertheless, this article does not advocate that in-person immersion of fieldwork should be replaced by alternative means or mediated ways, rather urges to consider the changing methodologies as choices not as necessity of conducting conventional ethnography. Social Science Review, Vol. 39(1), June 2022 Page 165-177